Penerapan SIMRS Dengan Knowledge Management System: Solusi Peningkatan Mutu Pelayanan Kesehatan - Muhammad Anwar; Asmawati Asmawati; Ranita Rizky Putri; Dimas Rifqi Anantyo; Agus Triyanto; Vip Paramarta (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2024)
Knowledge Management is a process that helps organizations to identify, choose, organize, share and transfer important information and experience which part from organization. Human Resources are one most important part in hospital. Every business process and services carried out by hospital require quality human service in their division. Knowledge in this information era very important for a company. The more knowledge that company employees have the more advance the company will be and pass on knowledge to the right people to improve company performance. The purpose of this theoretical analysis is to knowing the benefit of knowledge management in implementation and development hospital information management system and to knowing the software and hardware will need in this system. The research method used is a structured literature review via Google Scholar and Science Direct using keywords “knowledge management system, management hospital system”. Knowledge Management System in effective implementation should be considered supporting and inhibiting factors to maximize the system. It can be concluded that the application of SIMRS with Knowledge Management System can provide health services due to easy access to information, minimize risks in managing medical data and ensure the security of patient data, improve service coordination between medical personnel, provide accurate and timely health information for patients, and increase patient satisfaction. regarding the services provided by the Hospital.